Answer:
[12, 6, 30] → [a, b, c]
Explanation:
To start off, deal with the top two equations first and substitute 5b in for every c you see. Doing this substitution will give you this:
{a + 6b = 48 >> from the equation of a + b + 5b = 48
{9a + 34b = 312 >> from 9a + 14b + 4[5b] = 312
Then, use the elimination method:
-3⁄17[9a + 34b = 312]
{a + 6b = 48
{-1 10⁄17a - 6b = -55 1⁄17 >> New Equation
___________________
-10⁄17a = -7 1⁄17
______ ______
a = 12 [Plug this back into the equations above to get the b-term of 6, then the c-term of 30]; 6 = b, 30 = c
I am joyous to assist you anytime.